WOCAT SLM Approach: “Lessons learned from the "Mind the Gap" project: Improving Dissemination Strategies [Tunisia]” - Verbist, Joren; Rudiger, Udo; Najjar, Dina; Dhehibi, Boubaker; Derbel, Sondos (The Global Database on Sustainable Land Management (SLM) of WOCAT, 2024)
The WOCAT publication describes different ways of technology transfer like training and sending of SMS as well as subsidizing technologies and their contribution to technology adoption.